2009
DOI: 10.1111/j.1755-0998.2008.02462.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of storage type and time on DNA amplification success in tropical ungulate faeces

Abstract: The present study compares the effect of three storage media (silica, RNAlater®, ethanol) and time to extraction (1 week, 1 month and 3 months) on mitochondrial and nuclear marker amplification success in faecal DNA extracts from a sympatric community of small to medium-sized Central African forest ungulates (genera Cephalophus, Tragelaphus, Hyemoschus). The effect of storage type and time on nuclear DNA concentrations, genotyping errors and percentage recovery of consensus genotypes was also examined. Regardl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 43 publications
4
26
0
2
Order By: Relevance
“…As in other studies (Murphy et al, 2002; Santini et al, 2007; Soto-Calderon et al, 2009), we found that the storage time had a negative effect on the microsatellites amplification success, suggesting that the preservation medium could only retard but not stop the degradation of fecal DNA by endonucleases. We recommended that fecal DNA should be extracted as soon as the samples are collected in order to obtain high DNA quality, to increase the accuracy of microsatellite genotyping, and to decrease the associated cost.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As in other studies (Murphy et al, 2002; Santini et al, 2007; Soto-Calderon et al, 2009), we found that the storage time had a negative effect on the microsatellites amplification success, suggesting that the preservation medium could only retard but not stop the degradation of fecal DNA by endonucleases. We recommended that fecal DNA should be extracted as soon as the samples are collected in order to obtain high DNA quality, to increase the accuracy of microsatellite genotyping, and to decrease the associated cost.…”
Section: Discussionsupporting
confidence: 83%
“…The conclusions have, however, been inconsistent, even for the same preservation medium, suggesting that the optimal storage medium varies with species, environmental conditions, and other factors (Piggott & Taylor, 2003). Moreover, it was reported that the optimal storage types were dependent on the storage period (Murphy et al, 2002; Soto-Calderon et al, 2009), which could be the reason for the varied degradation rate of fecal DNA in different preservation media. Such observations necessitate the assessment of the storage type for each new fecal study.…”
Section: Introductionmentioning
confidence: 99%
“…Obtaining DNA isolates of sufficient quantity and quality from a single scat negates the need to isolate DNA from multiple pellets, as is sometimes required (e.g. Soto-Calderon et al 2009), thus minimizing the chance of sample contamination between different individuals. Screening DNA isolates for total DNA concentration allows inferior isolates (<0.25 ng/lL) to be discarded prior to genotyping and samples with sufficient amounts of DNA to be analysed using the minimum number of required replicates, thereby minimizing costs.…”
Section: Discussionmentioning
confidence: 99%
“…DNA isolated from faecal samples, however, may be associated with increased rates of amplification failure and genotyping error, in particular allelic dropout and false alleles (Bonin et al 2004;Pompanon et al 2005). Genotyping reliability may also be affected by scat storage (Frantzen et al 1998;Piggott & Taylor 2003a;Soto-Calderon et al 2009), sampling (Lampa et al 2008;Stenglein et al 2010) and isolation methods (Wehausen et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…2007). In a recent study, Soto‐Calderón et al. (2009) were able to amplify and successfully genotype unknown faecal samples from African forest artiodactyls using six published bovid microsatellite loci.…”
Section: Amplification Success and Detection Of Polymorphism In The mentioning
confidence: 99%